Perlindungan Hukum terhadap Perempuan dan Anak Korban Kekerasan dalam Rumah Tangga di Kabupaten Sidoarjo - Chairah, Dakwatul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2019)
Domestic violence (domestic violence) is a gender-based violence that can result in physical, psychological, sexual or mental suffering of women, including threats of similar actions, coercion or arbitrary deprivation of liberty, both in the public and private spheres. Domestic Violence rates in Sidoarjo Regency tend to increase and rank second in the province of East Java after the domestic violence case in Malang Regency. The cause's is economic, socio-cultural problems, the products of legislation that are gender biased and discriminatory, ignorance and community understanding of the contents of the domestic violence law. This condition is really alarming, and because of that, legal protection is needed for women and children who are victims of domestic violence. In addition, it is also necessary to strengthen their knowledge and understanding of the Domestic Violence Act to prevent the spread of domestic violence in the community and increase their awareness of domestic violence so as not to become victims of violence. Efforts to strengthen and understand the people of Sukodono Subdistrict, Sidoarjo Regency on the law are carried out with assistance. As a result, they are able to understand and practice domestic legislation in the settlement of domestic violence cases.